2018
DOI: 10.3892/ijo.2018.4391
|View full text |Cite
|
Sign up to set email alerts
|

Oct4 suppresses IR‑induced premature senescence in breast cancer cells through STAT3- and NF‑κB-mediated IL‑24 production

Abstract: Breast cancer stem cells (BCSCs) are a small subpopulation of breast cancer cells that have been proposed to be a primary cause of failure of therapies, including ionizing radiation (IR). Their embryonic stem-like signature is associated with poor clinical outcome. In the present study, the function of octamer-binding transcription factor 4 (Oct4), an embryonic stem cell factor, in the resistance of BCSCs to IR was investigated. Mammosphere cells exhibited increased expression of stemness-associated genes, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…A recent study shows that Oct-4 and c-myc can form a signal circuit to increase Adriamycin resistance in breast cancer [69]. Meanwhile, Kim et al have discovered that Oct-4 confers radiation resistance via STAT3 and NF-Bmediated IL-24 production in breast cancer cells [70]. In addition, paclitaxel is widely used as a clinical drug of breast cancer treatment, and phosphorylated STAT3 could mediate Survivin to promote paclitaxel resistance [71].…”
Section: The Role Of Stat3 In Breast Cancer Chemoresistancementioning
confidence: 99%
“…A recent study shows that Oct-4 and c-myc can form a signal circuit to increase Adriamycin resistance in breast cancer [69]. Meanwhile, Kim et al have discovered that Oct-4 confers radiation resistance via STAT3 and NF-Bmediated IL-24 production in breast cancer cells [70]. In addition, paclitaxel is widely used as a clinical drug of breast cancer treatment, and phosphorylated STAT3 could mediate Survivin to promote paclitaxel resistance [71].…”
Section: The Role Of Stat3 In Breast Cancer Chemoresistancementioning
confidence: 99%
“…ESCs share some characteristics with cancer stem cells such as the capability for self-renewal [ 21 , 22 ] and are therefore of high interest for cancer research. Cancer stem cells are described to have high tolerance towards DNA damage [ 5 ], robust cytoprotective pathways [ 5 ] and expression of ESCs factors such as octamer-binding transcription factor 4 (Oct4), which might confer them radioresistance [ 23 ]. In contrast, it has been previously shown that mESCs are more sensitive to irradiation with UV light or γ-rays than differentiated mouse embryonic fibroblasts (MEFs) [ 24 ], which might be explained by a more open chromatin configuration [ 24 , 25 ] and their high proliferation rate, which goes along with a short G1 phase of the cell cycle [ 5 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, triple-negative BCSCs in all IR doses significantly increased the expression of CD44 + /CD24 À/low surface markers, which has been related to radioresistance and poor prognosis in BC patients (Kim et al, 2016;Phillips Wang et al, 2017). In the same way, pluripotency (Kim et al, 2018;Takahashi and Yamanaka, 2006) and EMT-related gene (Theys et al, 2016;Zhou et al, 2011) differences observed for each cell line after treatment can be explained by the different sensitivity of BC molecular subtypes to IR (Kim et al, 2015). For the in vivo tumorigenic capacity after IR, the MDA-MB-231 TNBC cell line was chosen because of its described increased stemness properties, the potent migratory response, and aggressiveness in mice (Price et al, 1999).…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, triple‐negative BCSCs in all IR doses significantly increased the expression of CD44 + /CD24 −/low surface markers, which has been related to radioresistance and poor prognosis in BC patients (Kim et al , ; Phillips et al , ; Wang et al , ). In the same way, pluripotency (Kim et al , ; Takahashi and Yamanaka, ) and EMT‐related gene (Theys et al , ; Zhou et al , ) differences observed for each cell line after treatment can be explained by the different sensitivity of BC molecular subtypes to IR (Kim et al , ).…”
Section: Discussionmentioning
confidence: 99%